Exploring Sexual Health in Polish Adolescents – A School-Based Survey and Comparative Analysis - Sztajura, Jędrzej; Szot, Anna; Bujak, Monika; Chowaniec-Rybka, Katarzyna (Journal of Education, Health and Sport, 2025)
Introduction Sexuality is a complex area of study. That and the fact that the role of sex education in public health may have a potentially big impact, especially given safe sexual behaviour and sexually transmitted diseases (STDs), highlights the need for a better understanding of sexuality. This pilot study was aimed to explore the attitudes of Polish adolescents toward sexuality and sex education provided by family and school. Methodology The study employed a survey method and a questionnaire-based research technique, using an original anonymous questionnaire. The questions focused on sexual knowledge conveyed within the family environment of adolescents and in the schools they attended. Additionally, the questionnaire addressed individual experiences related to sexuality among adolescents. Results The study included 219 participants (100%). The largest group consisted of girls (173; 79%), while boys accounted for 46 participants (21%). However, only about one-third of them were satisfied with these conversations, and fewer than 8% expressed satisfaction with the sex education classes conducted at school. The Internet was mentioned most frequently as the source of knowledge about sexuality. More than two-thirds of the respondents admitted to having masturbated, but over 75% had not yet engaged in their first sexual activity with another person. Conclusion Sex education remains a sensitive topic for both parents and children. Among the subjects related to sexuality that participants found most interesting were: safe sexual behaviors, sexual maturation, the sexual needs of women and men, sexually transmitted diseases, and having children (pregnancy, childbirth). Sex education, especially when delivered through methods appealing to adolescents, continues to be a challenge for both the education system and the field of medicine, including public health.